Framework for a Pan-Arctic Network of MPAs: Cover Letter; PAME MPA-Network toolbox - Area-based conservation measures and ecological connectivity; and CAFF and PAME Arctic Protected Areas - Indicator report - Protection of the Arctic Marine Environment (PAME) (Arctic Council Secretariat, 2017)
The Network Toolbox focuses on area-based conservation measures as building blocks, summarizing key findings and recommendations from a science workshop (September 2016), as well as case studies submitted by AC States and PPs. The Network Toolbox focuses on area-based conservation measures as building blocks, summarizing key findings and recommendations from a science workshop (September 2016), as well as case studies submitted by AC States and PPs.